Development of RuO2/TiO2 titanium anodes and a device for in situ active chlorine generation - Spasojević Miroslav D.; Trišović Tomislav Lj.; Ribić-Zelenović Lenka; Spasojević Pavle M. (Hemijska Industrija, 2013)
Chlorine is used worldwide for water disinfection purposes. However, due to its toxicity the EU has imposed a set of standards that must be applied when transporting and storing chlorine. In Serbia, numerous studies have been conducted attempting to develop the technology for the generation of active chlorine disinfectant but with a non-toxic aqueous solution of sodium chloride as the raw material. This study provides an overview of the titanium anodes activated by thermally obtained solid solution of ruthenium and titanium oxide development. It also presents new findings on the effect of the temperature of thermal treatment, the composition, the thickness of an active coating on its microstructural properties, and consequently on the catalytic activity, ion selectivity, and corrosion stability during active chlorine generation through the electrolysis of dilute sodium chloride solutions at room temperature. The study also evaluates the effect of the kinetic and operational parameters of the electrochemical process of active chlorine generation on both current and energy efficiencies. The results obtained were used to determine optimal values of technological parameters of the production process. This comprehensive research resulted in the construction of different types of remote-controlled and fully automated active chlorine generating plants.